(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This study aims to determine: (1) the effect of sales promotion on impulsive purchases on Vinct Stuff products, (2) the effect of hedonic shopping value on impulsive purchases on Vinct Stuff products, (3) sales promotion on positive emotions on Vinct Stuff products, (4) ) the effect of hedonic shopping on positive emotions on Vinct Stuff products, (5) the effect of positive emotions on impulsive purchases on Vinct Stuff products, (6) the effect of sales promotions on impulsive purchases with positive emotions as mediation on Vinct Stuff products, (7) the effect hedonic shopping value on impulse buying with positive emotion as mediation on Vinct Stuff products. The sampling technique in this study used non-probability sampling with purposive sampling method. Data was obtained by distributing questionnaires online and filled in by 116 respondents. Data analysis used Partial Least Square (PLS) which was processed using SmartPLS 3.0. The results of this study indicate that: (1) Sales promotion has an effect on impulse buying on Vinct Stuff products, (2) Hedonic shopping value has no effect on impulse buying on Vinct Stuff products, (3) Sales promotion has an effect on positive emotion on Vinct Stuff products, (4) The value of hedonic shopping has an effect on positive emotions on Vinct Stuff products, (5) Positive emotions has an effect on impulsive purchases on Vinct Stuff products, (6) Sales promotions has an effect on impulsive purchases with positive emotions mediating some of the Vinct Stuff products, (7) Hedonic shopping value has an effect on impulsive buying with positive emotions fully mediating Vinct Stuff products.